(untitled) (Medico Legal Update, 2020)
In this study, Class 1 Integron co associated with some antibiotics resistant bacteria was investigated from different spots on Izmir bay of Aegean sea as a first report about analysis and track of influences human and animal wastes on water environment in a period between July 2019 – January 2020. Our results showed variations in Neomycin and Ciprofloxacin resistance bacteria, Neomycin resistance bacteria was detected in100 % of all sampling points ranged from 4.2×102 in (BOS) samples to 1.98×10 revealing wide distribution of Neomycin resistance bacteria in different spots on Izmir bay receiving sewage water. Ciprofloxacin resistance bacteria founded in 25 % of collected samples it was only founded in (BS) sampling point, Class 1 integron investigation, showed wide range distribution during sampling campaign among different sampling points, the main results showed that 75 % of samples was positive to class 1 integron presence, it was founded in Balçova Ilica (BS), Melez (MS), Bornova (BOS) points with no appear in the fourth point Bostanli streams (BTS). During the investigations we noticed that Class 1 integron elements was associated 100 % with Neomycin resistance bacteria in four sampling points (BS, MS, BOS & BTS) while showed weak association with Ciprofloxacin resistant bacteria.